Gut construction: scaffolds for intestinal tissue engineering - Majani, Ruby (2009)
Forming tissues in the laboratory to replace diseased or dysfunctional tissue or act as models for drug treatment is the goal of tissue engineering. The large intestine epithelium (colon surface) is a tissue which could benefit from both diseased and non-diseased models for the purpose of tackling colon cancer causes and treatments. Scaffolds (cell supports) are a pivotal part in many tissue engineering strategies. This thesis describes the design and production of two separate scaffolds based on the degradable polymer poly(lactic-co-glycolic acid) (PLGA). The first was a two dimensional scaffold to mimic the intestinal basement membrane which was modified with an oxygen plasma. The changes to the surface due to plasma and the degradation properties of the scaffold were extensively studied with SEM, XPS, AFM and GPC. The data showed that the oxygen plasma induced surface porosity and associated changes to surface roughness. The surface chemistry as detected by XPS was unchanged by both plasma treatment and degradation in buffered solution. The plasma treatment did lead to a dramatic loss in molecular weight but the degradation profile of both the untreated and etched films was similar. Extensive cell studies with SEM, live/dead, alamarBlue and Hoechst DNA assays showed that intestinal cells on the plasma treated scaffold was enhanced in terms of morphology, metabolic activity and proliferation. Finally, a two dimensional co-culture model using epithelial and myofibroblasts cell lines on the modified PLGA scaffold was achieved. The second scaffold was a three dimensional scaffold bearing the crypt like architecture of the colon. An accurate mould produced through electron beam lithography using dimensions measured from mouse histological sections. PLGA particles were used to fill the mould and sintered to produce the scaffold. A unique cell seeding approach using cell sheets was used. The cell sheets were produced on plasma polymers of acrylic acid and the discharge power was shown to affect surface wettability, chemistry and cell viability. The cell sheet approach proved to enhance cell attachment to the scaffold compared to individual cell seeding. Finally, a bilayer scaffold with model protein to mimic Wnt protein presence in the lower half of the crypt was studied with ToF-SIMS.